Acute gastric volvulus due to congenital bands in a newborn case - Soyer, Tutku; Özgün-Arlı, Ayşe; Öztürk, Haluk; Kaya, İbrahim Sefa (The Turkish Journal of Pediatrics, 2008)
Acute gastric volvulus in the newborn period is a rare condition requiring surgery. The association of gastric volvulus with congenital bands is extremely rare and unreported previously. A one-day-old male neonate was diagnosed to have acute gastric obstruction in the neonatal intensive care unit. Mesenteroaxial gastric volvulus due to dense gastrocolic bands was detected during laparotomy. Band excision and anterior gastropexy were performed. The clinical features, radiologic findings, treatment modes and possible mechanisms of gastric volvulus due to congenital bands are discussed.